Multiple Myeloma and B Cell Lymphoma. Investigation of IL-6, IL-6 Receptor Antagonist (IL-6RA), and GP130 Antagonist (GP130A) Using Various Parameters in an In Vitro Model - Eva Kovacs (The Scientific World Journal)
Interleukin-6 (IL-6) affects the survival and proliferation of myeloma cells via autocrine and/or paracrine mechanisms. In this study, we investigated the effects of IL-6, IL-6 receptor antagonist (IL-6RA), and gp130 antagonist (gp130A) on the membrane expressions of IL-6R and gp130, on the viability, on the proliferation, on the DNA synthesis, and on the cell cycle phases in several multiple myeloma (MM) cell lines and B cell lymphoma cell lines. Our results showed that (1) all five MM cell lines (OPM-2, RPMI-8226, U-266, KMS-12-BM, MOLP-8) expressed surface IL-6R and gp130, the B cell lymphomas (WSU-1, DOHH-2, U-698) expressed only gp130; (2) exogenous IL-6 markedly up-regulated the expression of membrane IL-6R (up to 186%) and down-regulated the gp130 receptor (down to 4%) in MM cell lines, the membrane expression of gp130 in B cell lymphomas was not altered; (3) IL-6 markedly increased the spontaneous proliferation (up to 151%) in all MM cell lines, that of B cell lymphomas was not affected; (4) IL-6 increased the DNA synthesis in the S cell cycle phase of MM cells and arrested the stage G2/M, IL-6 was ineffective in any cell cycle phase of B cell lymphoma; (5) IL-6RA inhibited the membrane IL-6R partially, the proliferation was decreased only slightly; and (6) although gp130A inhibited the membrane gp130 completely, the proliferation was decreased 81—78% in MM and B cell lymphoma cell lines. This means that gp130 is not absolutely necessary for the cellular signalling cascade via JAK/STAT and RAS/MAPK pathways involved in proliferation and viability. Our results give an indication in the therapy of MM: IL-6 antibody (IL-6A) alone or in combination with IL-6RA. The latter could be more effective. This kind of therapy is not recommended for B cell lymphoma, as these cells have no IL-6R.